Glucose and leukocyte esterase levels are possible biomarkers for bacterial septic arthritis - Jorge A. Gonzalez-Chapa; Víctor M. Peña-Martínez; Gloria M. Gonzalez; José F. Vílchez-Cavazos; Rogelio J. Treviño-Rangel; Mario C. Salinas-Carmona; Adrian G. Rosas-Taraco (Cirugía y Cirujanos, 2022)
Objective: The objective of the study was to determine the added value of synovial fluid (SF) glucose levels and other biochemical parameters as possible biomarkers of bacterial septic arthritis (SA). Materials and methods: We prospectively examined adult patients with SA. As a control group, adults with uninfected joints were enrolled. SF samples were obtained, and microbiological analyses were made. SF glucose levels, pH, and leukocyte esterase were measured using a glucometer and colorimetric test strips. Blood samples were collected from both groups to determine glucose levels. Results: We included eight subjects with knee ligaments lesions, six with meniscus lesions, and five with osteoarthritis as the control group, as well as 20 patients with SA. SF culture was positive in 60%. SF glucose levels from patients were lower than the controls (p = 0.0018) with the lowest concentration in patients with a positive culture (p = 0.0004). Blood and SF glucose concentration from the positive culture patients were compared (p < 0.0001). Leukocyte esterase presented the highest values in patients with a positive culture (p < 0.0001) and a more acidic pH was found compared to the control group (p < 0.0001). Conclusion: These biochemical parameters might be a quick and inexpensive added value for distinguishing between infective and non-infective joint disease.